Capital amnesty: pros and cons ("Journal "U". Economy. Management. Finance.", 2024)
The article is devoted to the analysis of the institution of capital amnesty as a mechanism of legalization of assets in the shadows, taking into account its legal framework and practical implementation in Russia. The article considers the stages of the amnesty, starting from 2015, and offers a detailed review of the arguments for and against the amnesty. The article is addressed to specialists in the field of financial law, economists and representatives of government agencies engaged in policy-making in the field of declaration and repatriation of capital.
Keywords: capital amnesty; voluntary declaration; asset legalization; tax violations; repatriation of capital; tax transparency; beneficial owners; investment climate; foreign assets; sanctions restrictions; money laundering